Answer:
The answer to your question is 3x - y = 3P - Q
Explanation:
Process
1.- Get the points from the graph of the original line
A (0, 5)
B (-3, 6)
2.- Find the slope of the original line
![m = (y2 - y1)/(x2 - x1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/cde6kt379flhu0nxn51l8r41msi803w4wf.png)
Substitution
![m = (6 - 5)/(-3 - 0) = (-1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/8bk7s83kc9r25kx1ue3tmujwl9g1s3cwr8.png)
3.- Find the slope of the new line
As the lines are perpendicular the new slope will be
m = 3
4.- Find the equation of the new line
Point (P, Q)
Equation y - y1 = m(x - x1)
Substitution
y - Q = 3(x - P)
Simplify
y - Q = 3x - 3P
Result
3x - y = 3P - Q